2019
DOI: 10.1108/ara-12-2017-0190
|View full text |Cite
|
Sign up to set email alerts
|

Audit committee chair accounting expertise and audit report timeliness

Abstract: Purpose The purpose of this paper is to investigate whether the characteristics of the audit committee (AC) chair affect audit report timeliness. In particular, the direct association between AC chair accounting expertise and audit report delay, and the moderating effect of other characteristics of AC chair on this association are examined. Design/methodology/approach To achieve the purpose of this study, the characteristics examined by this study are AC chair expertise, shareholding, tenure and multiple dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 92 publications
(179 reference statements)
4
80
0
10
Order By: Relevance
“…Firstly, the Corporate governance control variables, namely, board of directors' effectiveness (BDE) and audit committee effectiveness (ACE); secondly, the firm characteristics control variables, namely, firm size (SIZE), firm performance (ROA), leverage (LEV), and firm age (AGE). Prior studies have uncovered that those variables are associated with audit report lag (Knechel & Sharma, 2012;Dao & Pham, 2014;Hassan, 2016;Meckfessel & Sellers, 2017;Samaha & Khlif, 2017, Habib & Muhammadi, 2018Farag, 2017;Wan Hussin, Bamahros, & Shukeri,2018;Abdillah, Mardijuwono, & Habiburrochman, 2019;Mathuva, Tauringana, & Owino, 2019;Aljaaidi, Omer, & Bagulaidah, 2019;Baatwah, Salleh, & Stewart, 2019;Chae, Nakano, & Fujitani, 2020;Ha, & Nguyen, 2020;.…”
Section: Final Sample 198mentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the Corporate governance control variables, namely, board of directors' effectiveness (BDE) and audit committee effectiveness (ACE); secondly, the firm characteristics control variables, namely, firm size (SIZE), firm performance (ROA), leverage (LEV), and firm age (AGE). Prior studies have uncovered that those variables are associated with audit report lag (Knechel & Sharma, 2012;Dao & Pham, 2014;Hassan, 2016;Meckfessel & Sellers, 2017;Samaha & Khlif, 2017, Habib & Muhammadi, 2018Farag, 2017;Wan Hussin, Bamahros, & Shukeri,2018;Abdillah, Mardijuwono, & Habiburrochman, 2019;Mathuva, Tauringana, & Owino, 2019;Aljaaidi, Omer, & Bagulaidah, 2019;Baatwah, Salleh, & Stewart, 2019;Chae, Nakano, & Fujitani, 2020;Ha, & Nguyen, 2020;.…”
Section: Final Sample 198mentioning
confidence: 99%
“…With regard to the corporate governance control variables, we include the board of directors' effectiveness BDE (board size and meetings) and audit committee effectiveness ACE (audit committee size and meetings). Most prior archival studies have documented that the effectiveness of the corporate governance mechanisms is associated with audit report lag (DeZoort, Hermanson, & Archabeault 2002;Baatwah, Salleh, & Ahmad, 2015;Hassan, 2016;Farag, 2017;Samaha & Khlif, 2017;Oussii & Taktak, 2018;Wan Hussin et al 2018;Mathuva, et al, 2019;Aljaaidi et al, 2019;Baatwah et al, 2019;Abdillah, Mardijuwono, & Habiburrochman, 2019;Dang, Pham, Nguyen, & Nguyen,2020). With regard to the firm-specific control variables, prior studies have documented that the company size (SIZE), company performance (ROA), leverage (LEV), and company age (AGE) are significantly associated with audit report lag.…”
Section: Final Sample 198mentioning
confidence: 99%
“…Malaysian-listed companies have four months to produce their audited financials (published in an annual report) rather than the standard three months in other markets" (CLSA and ACGA, 2016). Furthermore, prior studies have shown that in Malaysia, the average ARL is 100 days as opposed to an average of between a minimum of 40 days to a maximum of 80 days in other developed and developing nations (Baatwah, Salleh, & Stewart, 2019;Mohamad-Nor, Shafie, & Wan-Hussin, 2010;Wan-Hussin, Bamahros, & Shukeri, 2018). Therefore, improvements in ARL can pose a notable impact on the timeliness of the audited financial reports (Dong, Robinson, & Xu, 2018), thereby leading to their enhanced timeliness in issuance.…”
Section: Introductionmentioning
confidence: 99%
“…However, merely a small number of published works in Malaysia have empirically looked into the role of the ACC on ARL. In Malaysia, Baatwah et al (2019) are the only researchers who have explored the association between the ACC who has the accounting expertise and ARL. Regardless, the current work is essentially an extension of Baatwah et al (2019), but with some differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation